Plan‐form evolution of ancient meandering rivers reconstructed from longitudinal outcrop sections. Issue 4 (27th February 2014) - Ghinassi, Massimiliano; Nemec, Wojciech; Aldinucci, Mauro; Nehyba, Slavomir; Özaksoy, Volkan; Fidolini, Francesco; Mountney, Nigel
Abstract The mode of channel‐bend transformation (i.e. expansion, translation, rotation or a combination thereof) has a direct bearing on the dimensions, shape, bedding architecture and connectivity of point‐bar sandstone bodies within a fluvial meander belt, but is generally difficult to recognize in vertical outcrops. This study demonstrates how the bend transformation mode and relative rate of channel‐floor aggradation can be deciphered from longitudinal outcrop sections aligned parallel to the meander‐belt axis, as a crucial methodological aid to the reconstruction of ancient fluvial systems and the development of outcrop analogue models for fluvial petroleum reservoirs. The study focuses on single‐storey and multi‐storey fluvial meander‐belt sandstone bodies in the Palaeogene piggyback Boyabat Basin of north‐central Turkey. The sandstone bodies are several hundred metres wide, 5 to 40 m thick and encased in muddy floodplain deposits. The individual channel‐belt storeys are 5 to 9 m thick and their transverse sections show lateral‐accretion bed packages representing point bars. Point bars in longitudinal sections are recognizable as broad mounds whose parts with downstream‐inclined, subhorizontal and upstream‐inclined bedding represent, respectively, the bar downstream, central and upstream parts. The inter‐bar channel thalweg is recognizable as the transition zone between adjacent point‐bar bedsets with opposing dip directions into or out of the outcrop section. The diverging or converging adjacent thalweg trajectories, or a trajectory migrating in up‐valley direction, indicate point‐bar broadening and hence channel‐bend expansion. A concurrent down‐valley migration of adjacent trajectories indicates channel‐bend translation. Bend rotation is recognizable from the replacement of a depositional riffle by an erosional pool zone or vice versa along the thalweg trajectory. The steepness of the thalweg trajectory reflects the relative rate of channel‐floor aggradation. This study discusses further how the late‐stage foreland tectonics, with its alternating pulses of uplift and subsidence and a progressive narrowing of the basin, has forced aggradation of fluvial channels and caused vertical stacking of meander belts.